1992
DOI: 10.1210/mend.6.6.1379672
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DNA sequences required for pituitary-specific expression of the glycoprotein hormone alpha-subunit gene.

Abstract: Transient transfection studies have been used to determine the DNA sequences of the glycoprotein hormone alpha-subunit gene that are required for tissue-specific expression. In the initial phase of these studies, a variant mouse alpha gene was identified which contains a fully palindromic cAMP response element (CRE). The corresponding region of a previously cloned and sequenced mouse alpha gene contains a single point mutation that disrupts the symmetrical nature of this element. DNase footprint studies demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
34
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 1 publication
3
34
0
Order By: Relevance
“…By exchanging the palindromic CREs of the human ␣ subunit promoter with a species variant of the element, we demonstrated that the sequence requirements for this element are different between the two cell types, an observation supported by a number of earlier findings (7,15,26). Together, these reports support the conclusion that the variant CRE is compatible with expression of the ␣ subunit gene in gonadotropes but not in trophoblasts.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…By exchanging the palindromic CREs of the human ␣ subunit promoter with a species variant of the element, we demonstrated that the sequence requirements for this element are different between the two cell types, an observation supported by a number of earlier findings (7,15,26). Together, these reports support the conclusion that the variant CRE is compatible with expression of the ␣ subunit gene in gonadotropes but not in trophoblasts.…”
Section: Discussionsupporting
confidence: 81%
“…Earlier studies using DNase footprinting or EMSA disclosed that the ␣ subunit CREs are occupied by proteins in both trophoblasts and gonadotropes, but the proteins were not identified (8,5,12,15,16,21). Steger et al (29) showed that purified CREB binds to the human ␣ subunit promoter and, with much lower affinity, to the mouse and equine ␣ subunit promoters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we identified DNA sequences which are important for pituitary-specific expression of the mouse a promoter (43,44). These studies found that sequences between -344 to -300 were sufficient and necessary to direct maximal expression of the mouse a-subunit promoter to cells of the gonadotrope and thyrotrope lineages.…”
mentioning
confidence: 99%
“…However, a shorter fragment ( 500 bp) seemed to be sufficient for full expression of the human -subunit gene in pituitary cell lines: the basal expression was not affected by deletion from 1800 to 442 bp upstream of the transcription start site of the gene (Horn et al 1992), but expression was reduced with loss of promoter sequences between -442 and -391 bp (Schoderbek et al 1992). This part of the promoter contains a pituitary glycoprotein hormone basal element (PGBE) which is able to function as a thyrotroph/ gonadotroph-specific enhancer (Aylwin & Burin 1995).…”
Section: Discussionmentioning
confidence: 98%